Сurrent trends in the production of milk-vegetable pastes - Pivtoratska, Angelina; Mykhalevych, Artur; Osmak (Fedchenko), Tetiana; Bandura (Kuzmyk), Uliana (My University, 2023)
Sour milk pastes occupy an important place in the diet of all segments of the population, which is due to their high nutritional value, namely the content of easily digestible complete milk protein, vitamins, mineral elements and dietary properties. With the change in taste preferences of consumers, there is a change in nutritional requirements.
Keywords: production of milk-vegetable pastes; beet; кафедра технології молока і молочних продуктів